2023
DOI: 10.21676/23897856.5073
|View full text |Cite
|
Sign up to set email alerts
|

TPACK para la implementación de recursos educativos digitales: una revisión sistemática

Gregorio Alberto Peña Coronado,
Tulio Enrique Cano Velásquez

Abstract: La educación basada en las tecnologías se exigen competencias docentes que integran sus conocimientos disciplinares y pedagógico con los entornos tecnológicos, ante esta realidad educativo el presente estudio describe las tendencias sobre el TPACK (Technological Pedagogical and Content Knowledge) para la implementación de recursos educativos digitales. Se enmarca en la revisión sistemática de la literatura partiendo de la pregunta ¿cuáles son las tendencias relacionadas al TPACK desde práctica docente al imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Robles et al (2019) found that students believed that incorporating WhatsApp into their academic lives contributed highly to communication among peers and faculty. This perception enables the learner's active participation in their learning process, turning knowledge into something meaningful; the researchers concluded, "How a teacher intervenes inside a WhatsApp group encourages or discourages students' interactions" (p. 245), revealing the importance of the educator's role in virtual scenarios and how their guidance and technological knowledge can positively or negatively influence the conditions mediating the learning process (Camacho Vásquez et al, 2023;Peña Coronado & Cano Velásquez, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Robles et al (2019) found that students believed that incorporating WhatsApp into their academic lives contributed highly to communication among peers and faculty. This perception enables the learner's active participation in their learning process, turning knowledge into something meaningful; the researchers concluded, "How a teacher intervenes inside a WhatsApp group encourages or discourages students' interactions" (p. 245), revealing the importance of the educator's role in virtual scenarios and how their guidance and technological knowledge can positively or negatively influence the conditions mediating the learning process (Camacho Vásquez et al, 2023;Peña Coronado & Cano Velásquez, 2023).…”
Section: Introductionmentioning
confidence: 99%